Examining the standalone efficacy and safety of tranexamic acid in chronic subdural hematoma: a comprehensive review and meta-analysis - Syed Muhammad Sinaan Ali; Abdul Haseeb; Muhammad Ashir Shafique; Muhammad Saqlain Mustafa; Aashish Kumar; Rabia Nasir; Muhammad Abdullah Bin Azhar; Tagwa Kalool Fadlalla Ahmad; Adarsh Raja; Sandesh Raja; Brandon Lucke-Wold (Egyptian Journal of Neurosurgery)
Abstract Background Chronic subdural hematoma (CSDH) is an important medical condition characterized by the accumulation of blood in the subdural space. Several methods have been explored, including surgical intervention and administration of tranexamic acid, which is a conservative treatment option. This meta-analysis aimed to assess the effectiveness and safety of tranexamic acid in CSDH management. Methods A systematic literature search was performed according to the PRISMA and MOOSE guidelines. This study included cohort and randomized controlled trials involving adults with chronic subdural hematoma (CSDH) who were treated with intravenous tranexamic acid. The primary outcome measures were recurrence and adverse events. Results Six studies encompassing 2024 participants were included. Studies have shown that tranexamic acid reduced recurrence rates (OR, 0.32; 95% CI: 0.27–0.38, p = 0.16; I2 = 0%), although the result was non-significant. However, the analysis of adverse events indicated a moderate level of heterogeneity (OR, 1.14; 95% CI: 0.60–2.15, p = 0.07; I2 = 57%), suggesting a potential safety concern. Conclusion In conclusion, this meta-analysis suggests tranexamic acid (TXA) may reduce chronic subdural hematoma (CSDH) recurrence, though significance varied across studies. Adverse effects with TXA were similar to controls. Larger trials are needed to confirm TXA’s role in CSDH management.